2013
DOI: 10.1080/02699931.2013.835254
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and validation of the attentional control scale

Abstract: The Attentional Control Scale (ACS; Derryberry & Reed, 2002) has been used to assess executive control over attention in numerous studies, but no published data have examined the factor structure of the English version. The current studies addressed this need and tested the predictive and convergent validity of the ACS subscales. In Study 1, exploratory factor analysis yielded a two-factor model with Focusing and Shifting subscales. In Study 2, confirmatory factor analysis supported this model and suggested su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
142
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 48 publications
14
142
2
Order By: Relevance
“…Self-reported attentional control was measured using the 20-item Attentional Control Scale (ACS-NL; Derryberry & Reed, 2002;Verwoerd, Cieraad, & de Jong, 2007). The ACS shows adequate psychometric properties (Judah, Grant, Mills, & Lechner, 2014). Finally, the 25-item Dutch Resilience Scale (RS-NL; Portzky, 2008;Wagnild & Young, 1993) was used to take into account self-reported levels of resilience.…”
Section: Questionnairesmentioning
confidence: 99%
“…Self-reported attentional control was measured using the 20-item Attentional Control Scale (ACS-NL; Derryberry & Reed, 2002;Verwoerd, Cieraad, & de Jong, 2007). The ACS shows adequate psychometric properties (Judah, Grant, Mills, & Lechner, 2014). Finally, the 25-item Dutch Resilience Scale (RS-NL; Portzky, 2008;Wagnild & Young, 1993) was used to take into account self-reported levels of resilience.…”
Section: Questionnairesmentioning
confidence: 99%
“…On the first step, all three DASS-21 factors (depression, anxiety, and stress) were entered because research has shown emotion to be associated with procrastination (Derryberry & Reed, 2002;Judah, Grant, Mills, & Lechner, 2014). On the second step, the four factors of the MCQ-30 that had been found to be significantly correlated with decisional procrastination were added to the model.…”
Section: Hierarchical Regression Analysis With Decisional Procrastinamentioning
confidence: 99%
“…The Attentional Control Scale (ACS) is a questionnaire that has been developed to measure individual differences in attentional control. The Attentional Control Scale is a 20-item self-report measure assessing attentional focusing and shifting (Judah, 2014). Both outcome measurements were measured at baseline and after 4 weeks, for all participants.…”
Section: Outcome Measurementsmentioning
confidence: 99%